2020
DOI: 10.1186/s12884-020-2766-9
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness, complication readiness and associated factors among pregnant women in Agnuak zone, Southwest Ethiopia: a community based comparative cross-sectional study

Abstract: Background: Birth Preparedness and Complication Readiness interventions have a significant role in the reduction of maternal and neonatal mortality risk. Inadequacy of birth and emergency preparedness were depicted as one of the major reasons for high maternal deaths in sub-Saharan Africa. The main objective of this study was to assess birth preparedness, complication readiness and associated factors among pregnant women. Methods: A community based comparative cross-sectional study design was conducted among 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 9 publications
3
21
1
Order By: Relevance
“…According to this study, the overall knowledge of obstetric danger signs was found to be 16.8%. Our study’s finding is in line with studies from Uganda, 9 Ethiopia Somali region, 16 Agnuak Zone, Southwest Ethiopia, 31 and Bench Maji Zone, Southwest Ethiopia 32 where 19.0%, 15.5%, 20.0%, and 14.6% were knowledgeable about obstetric danger signs, respectively. However the finding is lower than the studies conducted in different regions of Ethiopia: Arba Minch town (68.4%), 21 Yirgachaffe town (21.9%), 23 Debra-Birhan town (38.6%), 10 East Gojjam Zone (55.1%), 33 and Farta district (23.1%).…”
Section: Discussionsupporting
confidence: 91%
“…According to this study, the overall knowledge of obstetric danger signs was found to be 16.8%. Our study’s finding is in line with studies from Uganda, 9 Ethiopia Somali region, 16 Agnuak Zone, Southwest Ethiopia, 31 and Bench Maji Zone, Southwest Ethiopia 32 where 19.0%, 15.5%, 20.0%, and 14.6% were knowledgeable about obstetric danger signs, respectively. However the finding is lower than the studies conducted in different regions of Ethiopia: Arba Minch town (68.4%), 21 Yirgachaffe town (21.9%), 23 Debra-Birhan town (38.6%), 10 East Gojjam Zone (55.1%), 33 and Farta district (23.1%).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, one recent study in southwest Ethiopia reported that three-fourth of pregnant women were not counselled on all components of BPACR. 33 Therefore, it is possible that an increase in frequency of ANC visits per se may not result in better BPCR. Increased BPCR awareness in women could be promoted by healthcare workers during ANC visits…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is however, inconsistent with that of other studies where women in the third, fourth or fifth wealth quintiles were more likely to be prepared as compared with women in the lowest quintiles. 33 49 54 55 This means the odds of being well prepared for birth and its complications was significantly higher among women from high SES than those from low SES. In this case, the likely reasons could be that rich women having high income will be enabled to prepare for birth and its complications.…”
Section: Open Accessmentioning
confidence: 99%
“…These might have been influenced by the unique developmental stage of the city area of Tanzania, which recently became a middle-income country. Although ANC more than four times [ 21 – 23 ], first ANC within the first trimester [ 22 ], income [ 24 ], and age [ 24 26 ].showed significant relationships with BPR in previous studies, they were not found to be associated in this study.…”
Section: Discussionmentioning
confidence: 58%